Six new species of Rhaphidophora from China (Orthoptera: Rhaphidophoridae: Rhaphidophorinae) - Di, Mi; Qin, Yan-Yan; Shen, Zi-Hao; Zhang, Tao; Wang, Han-Qiang; Li, Kai; He, Zhu-Qing (European Journal of Taxonomy, 2024)
Six new species of the genus Rhaphidophora Serville, 1838 are described from China: R. hexagoniproctalis Wang, Di & He sp. nov., R. heterodentis Shen, Wang & He sp. nov., R. imbricofurca Shen, Wang & He sp. nov., R. glenoides Qin, Wang & He sp. nov., R. impressa Wang, Qin & He sp. nov., R. stenoterminata Zhang, Wang & He sp. nov. A key with previously described species from China is provided.